Trends in US emergency department visits and subsequent hospital admission among patients with inflammatory bowel disease presenting with abdominal pain: a real-world study from a national emergency department sample database - Zhijie Ding; Aarti Patel; James Izanec; Christopher D. Pericone; Jennifer H. Lin; Christopher W. Baugh (Journal of Market Access & Health Policy)
Background/Objective: This study evaluated emergency department (ED) visit trends, subsequent inpatient admissions for patients with inflammatory bowel disease (IBD) diagnosis and IBD-related abdominal pain (AP), and hospital-level variation in inpatient admission rates in the USA (US). Methods: This population-based, cross-sectional study included data from Nationwide Emergency Department Sample (NEDS, 2006─2013) database. Patients ≥18 years of age with primary ED diagnosis of IBD/IBD-related AP were included. Variables included demographics, insurance information, household income, Quan-Charlson comorbidity score, ED discharge disposition, and length of hospital stay (2006, 2010, and 2013). Variation between hospitals using risk-adjusted admission ratio was estimated. Results: Annual ED visits for IBD/100,000 US population increased (30 in 2006 vs 42 in 2013, p = 0.09), subsequent admissions remained stable (20 in 2006 vs 23 in 2013, p = 0.52). ED visits for IBD-related AP increased by 71% (7 in 2006 vs 12 in 2013; p = 0.12), subsequent admissions were stable (0.50 in 2006 vs 0.58 in 2013; p = 0.88). Proportion of patients with subsequent hospitalization decreased (IBD: 65.7% to 55.7%; IBD-related AP: 6.9% to 4.9%). Variation in subsequent inpatient admissions was 1.42 (IBD) and 1.96 (IBD-related AP). Conclusions: An increase in annual ED visits was observed for patients with IBD and IBD-related AP; however, subsequent inpatient admission rate remained stable.